CULTURAL SHOCK ENCOUNTERS IN HIGHER EDUCATION: A STUDY OF INDONESIAN STUDENTS’ EXPERIENCEC IN PAKISTAN - Nirwana, Nirwana; Syihabuddin, (English Language, Linguistics, and Culture International Journal, 2024)
This study explores the complex phenomena of academic culture shock that Indonesian students experience while they study in Pakistan. The main objective is to obtain a thorough grasp of the various aspects, contributing factors, and coping mechanisms related to academic culture shock in this particular group of students. In order to do this, the study makes use of well-established theoretical frameworks, such as Collen Ward's ABCs of culture shock paradigm, Rajasekar's model explaining the factors influencing culture shock, and Brislin's theory of cultural adjustment training. The study carefully examines the affective, behavioral, and cognitive aspects of academic culture shock that Indonesian students encounter through the use of qualitative research approaches. Important contributing factors include language obstacles, cultural differences in ethnicity, following new norms and traditions, and adjusting to seasonal changes. Moreover, the study emphasizes the critical role that initiation plays in the process of adaptation, whereby Indonesian students utilize comprehension, memorization, and self-directed task completion as essential coping strategies to negotiate and eventually overcome academic culture shock in the Pakistani educational setting.